Implementation of Odoo Enterprise Resource Planing (ERP) in the Jewelry Repair Process Using the Repair Module at XYZ Store - Ubaidillah, Fariz; Syaifudin; Siswanto, Teddy (Penerbitan Universitas Trisakti, 2026)
The jewelry repair sector continues to develop alongside increasing consumer demand for maintenance, resizing, and restoration services. However, many small and medium jewelry repair businesses still rely on manual administrative processes, resulting in inaccurate repair records, limited visibility of repair status, and delays in service completion. This study focuses on the implementation of an Odoo-based Enterprise Resource Planning (ERP) system by utilizing the Repair module as the core component to manage jewelry repair processes in a structured and integrated manner. The implementation is supported by related modules such as Inventory and Accounting to ensure material tracking and financial recording during the repair lifecycle. The Accelerated SAP (ASAP) methodology is applied, covering Project Preparation, Business Blueprint, Realization, and Final Preparation stages. The results demonstrate improvements in repair process efficiency, data accuracy, transparency of repair status, and real-time . This study concludes that the Odoo Repair module provides an effective solution for managing jewelry repair operations and recommends future research on automation of repair scheduling and customer notification systems.